2008
DOI: 10.3354/dao01880
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating freedom from Gyrodactylus salaris (Monogenea: Gyrodactylidae) in farmed rainbow trout Oncorhynchus mykiss

Abstract: This paper describes an approach to demonstrate freedom of individual rainbow trout farms from Gyrodactylus salaris Malmberg, 1957. The infection status of individual farms is relevant should G. salaris be introduced into a country or zone previously known to be free of the parasite. Trade from farms where G. salaris may have been introduced would be restricted until freedom had been demonstrated. Cage, fish and parasite sample sizes were calculated based on the minimum detectable prevalence (P*), test charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…[ 11 ], where the examination of formalin-preserved material in farm archives indicated that G. salaris had been in Italy on O. mykiss for at least nine years prior to discovery. Such asymptomatic hosts may represent a serious problem in that they can serve as reservoirs playing an important role in the epidemiology and dispersal of G. salaris across Europe [ 26 - 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ], where the examination of formalin-preserved material in farm archives indicated that G. salaris had been in Italy on O. mykiss for at least nine years prior to discovery. Such asymptomatic hosts may represent a serious problem in that they can serve as reservoirs playing an important role in the epidemiology and dispersal of G. salaris across Europe [ 26 - 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of these are highly virulent against Atlantic salmon, some strains that exhibit limited reproduction and are non‐pathogenic to Atlantic salmon have been isolated from other host species, including rainbow trout (Lindenstrøm et al, ) and Arctic charr (Olstad et al, ), which are more susceptible to infection. Establishing the infection status and, more specifically, demonstrating freedom from a strain of G. salaris pathogenic to Atlantic salmon in rainbow and brown trout, with low levels of prevalence and abundance, presents serious challenges (Peeler & Oidtmann, ). This study aimed to identify a compound that could be used in a non‐lethal procedure to remove gyrodactylid parasites from fish hosts and develop a robust method to rapidly recover detached parasites that can be used to screen the large numbers of fish that would be required for testing non‐primary hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Peeler and Oidtmann () detail a 3‐stage approach to structuring a survey on a rainbow trout farm which determines required sample sizes for rearing units (tanks or cages), fish within units and then parasites on individual fish to demonstrate freedom from G. salaris which may be present in mixed infections with other, non‐pathogenic, gyrodactylid species. When using the chemical approach, we simplify the survey structure by effectively sampling the tank‐level parasite population directly (assuming fish are selected at random for treatment).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary infections of the epidermal lesions with bacteria or fungi may also play a significant role in the pathogenicity of Gyrodactylus (58). The pathogenicity of G. salaris on some strains of Atlantic salmon Salmo salar became clear in the early 1970s, when this parasite was introduced into Norway with juvenile Atlantic salmon imported from Sweden for aquaculture (94).…”
Section: Introductionmentioning
confidence: 99%